2017
DOI: 10.1002/pbc.26638
|View full text |Cite
|
Sign up to set email alerts
|

No improvement in clinical trial enrollment for adolescents and young adults with cancer at a children's hospital

Abstract: Despite initiatives at CHP and on the national level to enroll more AYA patients on clinical trials, our most recent data show no improvement. This is a potentially remediable factor that needs to continue to be prioritized nationally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(43 citation statements)
references
References 25 publications
2
41
0
Order By: Relevance
“…Although CCTs existed nationally for more than half of our AYAs at both sites, CCTs were available for only one third as many AYAs at the adult cancer hospital. Although the overall low CCT enrollment of about 10% at both sites was not unexpected and is consistent with previous reports, 1,8,13,17 our findings of national-level similarity in CCT existence, but site-level disparity in CCT availability, are novel. They are significant because they demonstrate the need to account for treatment setting when considering solutions for the difficult problem of low CCT enrollment of AYAs.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although CCTs existed nationally for more than half of our AYAs at both sites, CCTs were available for only one third as many AYAs at the adult cancer hospital. Although the overall low CCT enrollment of about 10% at both sites was not unexpected and is consistent with previous reports, 1,8,13,17 our findings of national-level similarity in CCT existence, but site-level disparity in CCT availability, are novel. They are significant because they demonstrate the need to account for treatment setting when considering solutions for the difficult problem of low CCT enrollment of AYAs.…”
Section: Discussionsupporting
confidence: 92%
“…In addition to our recent prospective study of CCT availability within a children’s hospital, 14 we are aware of only three other reports of CCT availability for AYAs, two from one cancer center using internal data 13,15 and one from the NCI using population-based estimates. 18 All three of these studies were retrospective, detected relatively small effects, and yielded mixed results.…”
Section: Discussionmentioning
confidence: 99%
“…Similar patterns of lower accrual are now reported by other countries and despite different methodologies, sufficient evidence exists to support this as an international phenomenon . While lower inclusion in trials and research has been identified since the late 90s and is recognised as a universal issue, the evidence suggests that improvements in accrual reported by some countries have not been sustained and for most countries, no improvements are reported …”
Section: Introductionmentioning
confidence: 58%
“…We focused on melanoma and the time frames because of the recent improvements in survival on clinical trials leading to FDA approval of eight new agents from 2011 to 2016 . The overall therapeutic clinical trial enrollment rate found at this Comprehensive Cancer Center of 17.6% is higher than the reported national overall AYA clinical trial enrollment , but lower than enrollment at NCORP centers , or enrollments in 15‐ to 22‐year‐old patients in centers with an AYA program that has worked to increase trial enrollment . Among patients most likely to be eligible for therapeutic trial enrollment, 36% of metastatic patients and 34% of patients with unresectable or regional disease were treated on one of 83 available research protocols, approaching current pediatric oncology participation rates.…”
Section: Discussionmentioning
confidence: 99%
“…Among the myriad causes of this disparity are lower clinical trial participation rates than both pediatric and older adult patient cohorts; initially reported to be as low as 1–2% on cooperative group trials . The reasons for this being the lowest of any age range are likely multifactorial including suboptimal availability of trials at their location of care, trial awareness among providers and patients, regulatory factors, and a lack of recognition of this unique population of patients when developing therapies and trials When isolated to populations included in pediatric cooperative group trials at National Community Oncology Research Program centers, AYA enrollment on clinical trials is 24%, similar to a single institution study in this population . Retrospective data has also demonstrated that adolescent trial accrual is substantially higher, but not as high as the pediatric population, when adolescents are treated at pediatric institutions .…”
Section: Introductionmentioning
confidence: 98%